Salivary interleukin-17A and interferon-γ levels are elevated in children with food allergies in China - Yin, Yan; Ouyang, Shengrong; Li, Qin; Du, Yuyang; Xiong, Shiqiu; Zhang, Min; Wang, Wei; Zhang, Ting; Liu, Chuanhe; Gao, Ying (Frontiers in Immunology, 2023)
Introduction Food allergies have a substantial impact on patient health, but their mechanisms are poorly understood, and strategies for diagnosing, preventing, and treating food allergies are not optimal. This study explored the levels of and relationship between IL-17A and IFN-γ in the saliva of children with food allergies, which will form the basis for further mechanistic discoveries as well as prevention and treatment measures for food allergies. Methods A case–control study with 1:1 matching was designed. Based on the inclusion criteria, 20 case–control pairs were selected from patients at the Skin and Allergy Clinic and children of employees. IL-17A and IFN-γ levels in saliva were measured with a Luminex 200 instrument. A general linear model was used to analyze whether the salivary IL-17A and IFN-γ levels in the food allergy group differed from those in the control group. Results The general linear model showed a significant main effect of group (allergy vs. healthy) on the levels of IL-17A and IFN-γ. The mean IL-17A level (0.97 ± 0.09 pg/ml) in the food allergy group was higher than that in the healthy group (0.69 ± 0.09 pg/ml). The mean IFN-γ level (3.0 ± 0.43 pg/ml) in the food allergy group was significantly higher than that in the healthy group (1.38 ± 0.43 pg/ml). IL-17A levels were significantly positively related to IFN-γ levels in children with food allergies (r=0.79) and in healthy children (r=0.98). Discussion The salivary IL-17A and IFN-γ levels in children with food allergies were higher than those in healthy children. This finding provides a basis for research on new methods of diagnosing food allergies and measuring the effectiveness of treatment.